Artificial Intelligence: How Project Managers Can Leverage AI. - Yarbrough, Oliver (linkedin.com, 2021)
Learn practical ways to use AI in your projects, including how you can adapt to AI, leverage it to derive value from data, and follow emerging AI trends.